ROYALTY OF INDONESIAN SONGS COPYRIGHTS AT YAYASAN KARYA CIPTA INDONESIA ISSUED BY LAW NUMBER 19 OF 2002 ON COPYRIGHTS - Luh Putu Sudini (NOTARIIL Jurnal Kenotariatan, 2018)
Abstract This article aims at describing the role of Yayasan Karya Cipta Indonesia (YKCI) in copyright protection in Indonesia and the mechanism of royalty payment on Indonesian songs to the YKCI. Conceptual and statute approaches to legislation are the approach used in designing this study. Data were collected through library documentation. Data were analyzed qualitatively. The results show that YKCI's role as an administrator body in copyright protection is to collect royalties from parties that use songs or music commercially and help dispute resolution between creators, users or record producers of songs or music creations. Furthermore, the mechanism of royalty payments to YKCI shall be initiated by the authorization of YKCI by the creator or the copyright holder of the song, so on the basis of such power of attorney. Law Number 19 of 2002 on Copyright should be accompanied by the willingness and ability of the apparatus in enforcing it so that what to be achieved with the Act can be obtained. It is recommended that the government immediately issue provisions on the roles, duties and functions of the Copyright Council as well as the organic rules that explain the authority of YKCI which may be the appointment of the Director-General of Intellectual Property Rights (IPR) as endorsement of a collective society in order to attract royalties. Keywords: Royalty, Copyrights of Song, YKCI